Does drafting beat "bleeding"? : an action research investigation into the introduction of a cognitivist process approach to the teaching of writing at senior secondary level - McKellar, Elizabeth Jennifer Kelk (Rhodes University, Faculty of Education, Department of Education, 1996)
In this study an attempt is made to describe and illuminate the attitude of both pupils and teachers to the introduction of a cognitivist process approach to the teaching of written literacy in one standard in a multi-cuI tural Eastern Cape Model C secondary school. Because the cognitivist process approach to the teaching of written literacy was to complement already existing strategies for the teaching of written literacy, the research took the form of collaborative action research in three standard nine English classrooms. Teacher- and pupil diaries were the main means of data collection. Two spirals of action research were conducted in an attempt to identify difficulties and improve practice. Diaries and discussion revealed a positive response to the drafting, revision and editing processes which researchers had already identified as the processes which skilled writers use in creating text. Acknowledgement of the benefits to be derived from peer response as audience was also established. Anomalies relating to the grouping of pupils for peer-editing were found to be a key issue in determining the relative success of the project. Difficulties were also found to exist in the ability of some of the pupils to engage effectively in peer-peer and teacher-peer negotiation of text. Possible reasons for these difficulties have been identified , and further research into the nature of the inherent power relationships which exist implicitly in a multi-cultural educational setting and impede negotiation would be necessary to appreciate fully the difficulties experienced.
Keywords: Action research in education; English language -- Writing -- Study and teaching (Secondary)